Energy-efficient traction system of a locomotive with a multi-diesel power plant - Lysenko, Yevhen (National Technical University "Kharkiv Polytechnic Institute", 2024)
Research on the use of modern power plants on shunting locomotives has been analyzed. To reduce fuel consumption and the harmful impact on the environment, both hybrid and multi-diesel power plants are used.
Keywords: locomotives; diesels; rolling stock; energy efficiency; traction electric drive